2013
DOI: 10.3109/0142159x.2013.849333
|View full text |Cite
|
Sign up to set email alerts
|

Is the modernisation of postgraduate medical training in the Netherlands successful? Views of the NVMO Special Interest Group on Postgraduate Medical Education

Abstract: The discussion about the aims of modern medical education could benefit from a more structured and transdisciplinary approach. Research is warranted on the interface between health care provision and those sciences that specialise in generic professional skills and in the societal context. Training professionals and educating 'enlightened change agents' for transformation in health care requires more governance and support from academic leaders with a broader perspective on the future of health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…If these conditions are met, a safe learning environment can develop, providing residents with an optimum opportunity to learn (Teunissen 2011). The program director, who has a formal leading position within the teaching team, has to connect the individual expectations of team members and to promote a common understanding regarding residents' expected professional performance (Scheele et al 2014). It has been suggested that program directors are more focused on the task of teaching residents than giving attention to teamwork of clinical teachers.…”
Section: Introductionmentioning
confidence: 99%
“…If these conditions are met, a safe learning environment can develop, providing residents with an optimum opportunity to learn (Teunissen 2011). The program director, who has a formal leading position within the teaching team, has to connect the individual expectations of team members and to promote a common understanding regarding residents' expected professional performance (Scheele et al 2014). It has been suggested that program directors are more focused on the task of teaching residents than giving attention to teamwork of clinical teachers.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, details of generic models for CBME are not always explicitly outlined, which leads to a lack of clarity about its content, meaning, and relevance. [13][14][15][16][17] In addition, the implementation of CBME frameworks is further complicated by a lack of support from expert facilitators such as educationalists who can help with understanding the educational concepts and relating them to the clinical work environment. 6,18 Despite the challenges that PGME is facing with the implementation of CBME, attention to a change management perspective on supporting these processes is still rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in many countries trainee doctors are considered a valuable part of the workforce, and hence there is a political desire to ensure that the composition of postgraduate training programmes include training posts at non-university hospitals. Therefore, in PGME reforms issues of governance, organisation, and structure are always high on the agenda (The Danish Ministry of Health 2000; Wallenburg et al 2012;Scheele et al 2014). In several countries this is reflected in a move away from professional self-governance of PGME towards co-regulation by state, healthcare institutions, and professional bodies (The Danish Ministry of Health 2000; Malling 2011, Wallenburg et al 2012.…”
mentioning
confidence: 97%
“…In this issue, Scheele et al (2014) reflect on the modernisation of postgraduate medical training in the Netherlands from the perspective of three levels of learning -informative learning, formative learning and transformative learning. They report more or less successful implementation at the first level, aiming to create 'medical expertise' and the second level aiming at fostering professionalism.…”
mentioning
confidence: 99%
See 1 more Smart Citation